Vitamin D-Rich Diet in Mice Modulates Erythrocyte Survival - Elisabeth Lang; Kashif Jilani; Rosi Bissinger; Rexhep Rexhepaj; Christine Zelenak; Adrian Lupescu; Florian Lang; Syed M. Qadri (Karger Publishers, 2015)
Background/Aims: Epidemiological evidence suggests that vitamin D deficiency is associated with anemia. The potent metabolite 1,25(OH)2 vitamin D3 [1,25(OH)2D3] activates various signaling cascades regulating a myriad of cellular functions including suicidal cell death or apoptosis. Suicidal death of erythrocytes or eryptosis is characterized by cell shrinkage and cell membrane scrambling leading to phosphatidylserine (PS) externalization. Stimulation of eryptosis may limit lifespan of circulating erythrocytes and thus cause anemia. In the present study, we explored the effect of a high vitamin D diet (10,000 I.U. vitamin D for 14 days) in mice on eryptosis. Methods: Plasma concentrations of erythropoietin were estimated using an immunoassay kit, blood count using an electronic hematology particle counter, relative reticulocyte numbers using Retic-COUNT® reagent, PS exposure at the cell surface from annexin V binding, cell volume from forward scatter, and cytosolic Ca2+ ([Ca2+]i) from Fluo3-fluorescence in FACS analysis. Results: Vitamin D treatment decreased mean corpuscular volume, reticulocyte count, and plasma erythropoietin levels. Vitamin D treatment slightly but significantly decreased forward scatter but did not significantly modify spontaneous PS exposure and [Ca2+]i of freshly drawn erythrocytes. Vitamin D treatment augmented the stimulation of PS exposure and cell shrinkage following exposure to hyperosmotic shock (addition of 550 mM sucrose) or energy depletion (glucose removal) without significantly modifying [Ca2+]i. Conclusions: The present observations point to a subtle effect of exogenous vitamin D supplementation on erythrocyte survival.